Recent Advances in Microflow Photochemistry - Oelgemöller, Michael (Molecules, 2011)
This review summarizes recent advances in microflow photochemical technologies and transformations. The portfolio of reactions comprises homogeneous and heterogeneous types, among them photoadditions, photorearrangements, photoreductions, photodecarboxylations, photooxygenations and photochlorinations. While microflow photochemistry is most commonly employed as a micro-scale synthesis tool, scale-up and technical production processes have already been developed.